Mutant TDP-43 deregulates AMPK activation by PP2A in ALS models. - Nirma D Perera; Rebecca K Sheean; John W Scott; Bruce E Kemp; Malcolm K Horne; Bradley J Turner (PLoS ONE)
Bioenergetic abnormalities and metabolic dysfunctionoccur in amyotrophic lateral sclerosis (ALS) patients and genetic mouse models. However, whether metabolic dysfunction occurs earlyin ALS pathophysiology linked to different ALS genes remains unclear.Here, we investigatedAMP-activated protein kinase (AMPK) activation, which is a key enzyme induced by energy depletion and metabolic stress, inneuronal cells and mouse models expressing mutantsuperoxide dismutase 1 (SOD1)or TAR DNA binding protein 43 (TDP-43) linked to ALS.AMPKphosphorylation was sharply increased in spinal cords of transgenic SOD1G93A mice at disease onset and accumulated incytoplasmic granules in motor neurons, but not in pre-symptomatic mice. AMPK phosphorylation also occurred in peripheraltissues, liver and kidney, in SOD1G93A mice at disease onset, demonstrating that AMPK activation occurs late and is not restricted to motor neurons. Conversely, AMPK activity was drastically diminished in spinal cords and brains of presymptomatic and symptomatictransgenic TDP-43A315T mice and motor neuronal cells expressing different TDP-43 mutants. We show that mutant TDP-43 induction of the AMPK phosphatase,protein phosphatase 2A (PP2A), is associated with AMPK inactivation in these ALS models. Furthermore, PP2A inhibition by okadaic acid reversed AMPK inactivation by mutant TDP-43 in neuronal cells. Our results suggest that mutant SOD1 and TDP-43 exert contrasting effects on AMPK activation which may reflect key differences in energy metabolism and neurodegeneration in spinal cords of SOD1G93A and TDP-43A315T mice. While AMPK activation in motor neurons correlateswith progressionin mutant SOD1-mediated disease, AMPK inactivation mediated by PP2Ais associated withmutant TDP-43-linked ALS.